2007
DOI: 10.1021/np068065o
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Potential Cancer Chemopreventive Constituents of the Fruits of Morinda citrifolia (Noni)

Abstract: A new anthraquinone, 1,5,15-tri-O-methylmorindol (1), and two new saccharide fatty acid esters, 2-O-(beta-D-glucopyranosyl)-1-O-hexanoyl-beta-D-gluropyranose (4) and 2-O-(beta-D-glucopyranosyl)-1-O-octanoyl-beta-D-gluropyranose (5), have been isolated from a methanol extract of the fruits of Morinda citrifolia (noni) along with 10 known compounds, namely, two anthraquinones (2, 3), six saccharide fatty acid esters (6-11), an iridoid glycoside (12), and a flavanol glycoside (13). Upon evaluation of six compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 13 publications
0
31
0
3
Order By: Relevance
“…A number of major chemical compounds have been identified in the leaves, roots, and fruits of Noni plant (Pawlus et al, 2005;Akihisa et al, 2007;Alitheen et al,a first-line chemotherapeutic agent in the treatment of epithelial malignancies, including cancer of cervix, lung, ovarian, testicular, and others. It induces tumor killing by interacting with the DNA and activating mitogen-activated protein kinase (MAPK) signaling pathway, which controls a wide spectrum of cellular processes including growth, differentiation, and apoptosis (HernandezFlores et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A number of major chemical compounds have been identified in the leaves, roots, and fruits of Noni plant (Pawlus et al, 2005;Akihisa et al, 2007;Alitheen et al,a first-line chemotherapeutic agent in the treatment of epithelial malignancies, including cancer of cervix, lung, ovarian, testicular, and others. It induces tumor killing by interacting with the DNA and activating mitogen-activated protein kinase (MAPK) signaling pathway, which controls a wide spectrum of cellular processes including growth, differentiation, and apoptosis (HernandezFlores et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that products derived from the fruit of noni may have a wide range of potentially beneficial effects. For example, it is shown that noni fruit juice (NFJ) has anti-inflammatory and anticancerous activities (3,4). There is further evidence to demonstrate that NFJ inhibits angiogenic initiation and disrupts newly established human vascular networks (5), indicating its antiangiogenic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Teniendo en consideración que, posterior a todo procedimiento quirúrgico bucal aparece un episodio doloroso, existe plena justificación para la utilización de medicamentos que controlan y reducen la duración y grado de dolor posoperatorio (Becker;Jung et al;Romera et al, 2000). La evidencia de que el fruto de Noni presenta efecto analgésico proviene de experimentos en animales, realizados por Younos et al (1990), Punjanon & Nandhasri (2005), Akihisa et al (2007), Deng et al (2007) y Dussossoy et al (2011). Según recientes investigaciones, la inhibición de las vías metabólicas de ciclooxigenasa y lipooxigenasa pueden ser las responsables de este efecto (Wang et al;Akihisa et al;Palu et al, 2004Palu et al, , 2012.…”
Section: Discussionunclassified
“…La evidencia de que el fruto de Noni presenta efecto analgésico proviene de experimentos en animales, realizados por Younos et al (1990), Punjanon & Nandhasri (2005), Akihisa et al (2007), Deng et al (2007) y Dussossoy et al (2011). Según recientes investigaciones, la inhibición de las vías metabólicas de ciclooxigenasa y lipooxigenasa pueden ser las responsables de este efecto (Wang et al;Akihisa et al;Palu et al, 2004Palu et al, , 2012. Además, Younos et al, concluyeron que el fruto de Morinda citrifolia podría tener un efecto analgésico central, debido a que naloxona inhibió parcialmente su efecto.…”
Section: Discussionunclassified